The Effect of Leverage, Liquidity and Activity on Financial Distress with Profitability and Firm Size as Moderating Variables - Sukoco Ari Hartono; Yulia Efni; Enni Savitri (Indonesian Journal of Economics, Social, and Humanities, 2026)
Companies that have been operating for a certain period of time experience financial difficulties that lead to bankruptcy. Corporate bankruptcy does not occur suddenly but starts from financial distress (financial difficulties) because financial problems are an early sign that a company will experience bankruptcy. An analysis of the symptoms of bankruptcy must be carried out, in order to anticipate the occurrence of bankruptcy in the future. The way to do this is to analyze the company's financial ratios as in this study. This study aims to determine and analyze the effect of leverage, liquidity and activity on financial distress with profitability and firm size as moderating variables. In this study, the population is Manufacturing Companies listed on the Indonesia Stock Exchange in 2019-2020. From the total population, the sample was determined as many as 20 companies. The data used in this study are primary data and secondary data, while the data collection techniques for the company's financial statements. The data analysis technique in this research uses 2 methods of data analysis, namely multiple regression and Moderated Regression Analysis (MRA). Based on the results of the study, leverage and liquidity have a significant effect on financial distress. While the activity does not have a significant effect on financial. profitability is able to moderate the effect of leverage and liquidity on financial distress, but profitability does not moderate the effect of activity on financial distress. Negative and significant company size is able to moderate the effect of leverage and liquidity on financial distress, but company size does not moderate the effect of activity on financial distress.